x → 0 lim 1 2 x − 2 5 tan − 1 a + 4 8 tan − 1 ( a + x ) − 3 6 tan − 1 ( a + 2 x ) + 1 6 tan − 1 ( a + 3 x ) − 3 tan − 1 ( a + 4 x ) = ?
a ∈ R
Bonus: Evaluate this limit without using L'Hôpital's rule . More importantly, how do you interpret this limit?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thanks for the well explained solution. The limit indeed evaluates the derivative of tan − 1 x at x = a . This is another way of computing derivatives using first principles. I derived this formula using Taylor series up to 4th order accuracy. The order of accuracy becomes relevant in the context of numerical differentiation.
The general 4th order accurate formula (forward finite differences) for computing the derivative of a function is:
d x d f = h → 0 lim 1 2 h − 2 5 f ( x ) + 4 8 f ( x + h ) − 3 6 f ( x + 2 h ) + 1 6 f ( x + 3 h ) − 3 f ( x + 4 h )
You can test this for other continuously differentiable functions to verify.
Log in to reply
Aahh, I might have recognised that back when I was studying numerical analysis.
Problem Loading...
Note Loading...
Set Loading...
We can rewrite the limit as L = x → 0 lim [ 1 2 x 4 8 tan − 1 ( a + x ) − 4 8 tan − 1 a − 1 2 x 3 6 tan − 1 ( a + 2 x ) − 3 6 tan − 1 a + 1 2 x 1 6 tan − 1 ( a + 3 x ) − 1 6 tan − 1 a − 1 2 x 3 tan − 1 ( a + 4 x ) − 3 tan − 1 a ] = x → 0 lim 4 x tan − 1 ( a + x ) − tan − 1 a − x → 0 lim 6 2 x tan − 1 ( a + 2 x ) − tan − 1 a + x → 0 lim 4 3 x tan − 1 ( a + 3 x ) − tan − 1 a − x → 0 lim 4 x tan − 1 ( a + 4 x ) − tan − 1 a = x → 0 lim 4 x tan − 1 ( a + x ) − tan − 1 a − x 1 → 0 lim 6 x 1 tan − 1 ( a + x 1 ) − tan − 1 a + x 2 → 0 lim 4 x 2 tan − 1 ( a + x 2 ) − tan − 1 a − x 3 → 0 lim x 4 tan − 1 ( a + x 3 ) − tan − 1 a
We recognise these expressions as multiples of the derivative of tan − 1 ( X ) evaluated at X = a , which we know to be 1 + a 2 1 . So L = 1 + a 2 1 [ 4 − 6 + 4 − 1 ] = 1 + a 2 1